The education, training, and coaching of household businesses producers of Opak Gambir - Kustiani, Lilik; Isnuwardiati, Kurnia; Widiawati, Diah; Setyawati, Dyah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Selorejo Village, Blitar Regency is a village where some of the residents produce Opak Gambir snacks which are still managed using traditional methods. This causes the management in the production to be less professional and less organized. This program aims to improve education and training, especially in the fields of entrepreneurship, finance, and marketing, so that the management of this home industry will be more organized and professional. The method of implementing the program is by providing education, training, and coaching for producers. The results of the program show that the producer is very well educated about the principles of entrepreneurship. Opak Gambir producers are also able to make financial plans both for administration and also the selling price of their products. The producer is also able to determine marketing plans, which include starting from the process of determining prices, determining distribution locations, and how the promotion process is carried out. Through this community service, it is hoped that the producer will be able to manage their business in a professional manner, apart from being a source of income, is also a destination for the Opak Gambir industry.